Redescription of the longnose houndshark Iago garricki (Carcharhiniformes: Triakidae), based on specimens recently collected from the South China Sea - Ng, Shing-Lai; Ho, Hsuan-Ching; Liu, Kwang-Ming; Joung, Shoou-Jeng (Zootaxa, 2022)
The longnose houndshark, Iago garricki Fourmanoir & Rivaton 1979, was described based on five specimens collected from Vanuatu. Five additional specimens were recently collected from the waters off Dongsha Atoll, South China Sea. A redescription of this species is provided based on the holotype, non-types collected near the type locality and off Dongsha Atoll. The species is characterized by eye length larger than gill slit height; first dorsal-fin origin not reaching a vertical line through pectoral-fin base; head length 20.2–22.2% TL; preoral length 7.2–8.3% TL; upper labial furrow 2.2–3.4% TL; lateral teeth with 1–3 small cusplets on lateral side basally; diplospondylous centra 53–61; precaudal centra 94–102; and total centra 149–157. The specimens collected from the South China Sea represent the northernmost distributional record of this species.